Table of Content - -, (Journal of Curriculum and Teaching Methodology, 2025)
Table of Content:• Using ADDIE model to design an interactive booklet to introduce the clothing heritage of Asir  to late childhood girls in the Muhayil Asir Governorate in the year of 1444 – 2023Dr. Sahar Hassan Ejeimi, Ms. Aisha Hassan Alsheri• A proposed vision to improve learning outcomes in the field of natural sciences in light of the reasons for the low results of national tests (Nafi) In the Kingdom of Saudi ArabiaDr. Monahi Abdulrhman Moalwi, Dr. Abdullah Saeed Al-Shahrany ,Dr. Ahmad Mohammad Al Orij,Mr. Saad Mohammed Al-Khathami,Mr. Abdullah Ali Mughbash,Mr. Mohammed Mufarrih Al-Shahrani• The Educational Strategy for Developing Reading Skills among a Sample of Fifth Grade Students with Specific Learning DisabilitiesDr. Wael Maher Ghonim, Mr. Haitham Ishaq Al-Laham, Ms. Mona Mohammed Al-Naqbi• The role of the interactive board in improving Arabic writing skills for nonMs. Hind Abdullah Muhammad Alamri• The effectiveness of a program based on office activities in simplifying some Arabic grammar rules for early childhood childrenDr. Muna Abdullah Al-Anazi• The Role of Public School Teachers in East Jerusalem in Mainstreaming Students with Special NeedsMs. Rula Nemir Faries Ganem khatib
Keywords: Journal of Curriculum and Teaching Methodology